Cervical Sympathetic Chain Schwannomas: A Global Systematic Review Provides Insight on Diagnosis, Treatment, and Outcomes. (2nd September 2014) - Setzen, Gavin; Keefe, Michael A.; Sharghi, Leighla H.; Cho‐Reyes, Soojin; Howie, Benjamin A.; Navaie, Maryam
Abstract : Objectives: Systematically evaluate the diagnosis, treatment, and outcomes of globally published cases of cervical sympathetic chain schwannomas (CSCS) to guide clinical decision making. Methods: Using Medline, EMBASE, and Cochrane databases, 89 CSCS case reports/series were identified from 1997 to 2013. Most cases were treated internationally (82%), predominantly in Asia (50%) and Europe (27%). Demographic, clinical, and outcomes data were extracted by 2 independent reviewers with high interrater reliability (k = 0.79). P <. 05 denoted statistical significance. Results: On average, patients were 42.6 years old (SD = 13.3) and had a 2 to 4‐cm (52.7%) or >4‐cm (43.2%) neck mass. Nearly 70% of cases were asymptomatic. Presurgical diagnosis relied heavily on computed tomography (63.4%), magnetic resonance imaging (MRI; 59.8%), or both (20%), supplemented by cytology (47.6%). US‐treated cases were significantly more likely to receive pre‐surgical MRI than internationally treated cases, but less likely to have cytology or histopathology ( P <. 05). Presurgical diagnosis accuracy was only 11% as confirmed postsurgically. Extracapsular (complete) resection was more commonly performed than intracapsular resection (87.6%), irrespective of mass size and treatment country. Postsurgical adverse events (AEs) were more common with the extracapsular approach and when mass size was >4 cm. Reported AEs included Horner's syndrome (89.9%), First Bite syndrome (21.1%), or both (15.7%). AEs persisted in 81.1% of cases, with 28.8 months (SD = 27.1) average follow‐up time. Conclusions: Given the typical CSCS patient is young and asymptomatic, presurgical diagnostic accuracy is very low, and the likelihood of persistent postsurgical morbidity is high with aggressive extracapsular surgery, less invasive approaches to differentially manage CSCS are warranted.